Problematic internet usage self-regulation dilemmas: Effects of presentation format on perceived value of behavior. (May 2017) - Dunbar, David; Proeve, Michael; Roberts, Rachel
Abstract: A model of the dynamics of self-regulation describes two patterns of commitment or progress that individuals may follow when selecting goal directed behaviors. In the commitment pattern, individuals are more likely to highlight congruent goal behavior choices while in the progress pattern individuals are more likely to balance between incongruent and congruent goal behavior choices. This study set out to test the model in the context of problematic Internet usage. After being primed about problematic Internet usage, a sample of 97 undergraduate university students completed an online survey rating the value of Internet, academic and social-related behaviors across three conditions. The three conditions paired behaviors so that they appeared to complement each other, appeared to compete against each other, and presented them individually. Results showed that Internet behaviors were rated more highly when presented as complementary than when presented as competing, supporting the prediction that presentation format primes progress and commitment frameworks and leads to higher ratings of incongruent goal behavior in the progress condition. While results did not fully support the model's predictions regarding congruent goal behavior, they were in the predicted direction with small to moderate effect sizes. This study may inform clinical interventions by suggesting that individuals experiencing issues with problematic Internet usage would benefit from framing self-regulatory dilemmas in a competing format. Highlights: Goals can be represented as commitment to, or progress towards, a desired end state. Commitment and progress representations cause different behavior evaluations. Presentation formats (complementary or competing) primes representation frameworks. Self-regulation dilemmas would benefit from framing behaviors in a competing format.